WAKAF SAHAM DITINJAU DARI HUKUM ISLAM DAN PERATURANPERUNDANG-UNDANGAN SETELAH BERLAKUNYA UNDANG-UNDANG NOMOR 41 TAHUN 2004 TENTANG WAKAF - Havita, Gusva; Hakim, Gestivia (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2017)
Wakaf as a religious institution, in addition to functioning as a means of worship also has a social function. And over the course of time and the birth of modern Islamic society, the waqf also experienced a dynamic development as well. One of the issues of contemporary waqf in the study of jurisprudence of wakaf is about the extension of wakaf coverage which includes moving objects, one of which is stock. The transfer of shares for the purpose of wakaf is called the stock wakaf. To obtain a comprehensive analysis of the stock wakaf, the authors analyzed two main issues concerning the reasons for endowments of shares allowed under Islamic law, and Islamic laws review of the provisions of shares as an object of wakaf in the legislation after the enactment of Law No. 41 of 2004 on Wakaf . In analyzing the two main issues, the author uses descriptive method to produce descriptive analytical thesis. This study yields the conclusion that Islamic jurisprudence expert and Islamic Law Compilation, wakaf share is allowed to remember shares have conservation benefit that is in the form of dividend that can be picked up as long as the issuer company runs its business well and get profit, while the principal value of stock is maintained. Similarly, the MUI Fatwa dated May 11, 2002 on Waqf of money also permits the wakaf of shares because it sees the similarity between money and stocks, which has great potential benefits when it is represented. The review of Islamic law on shares as an object of wakaf in the legislation after the enactment of Law No. 41 of 2004 on Waqf, the conclusion that Sharia and conventional shares of halal / mubah companies may be used as wakaf objects. The permissibility of the conventional stock of the halal / mubah company to be the object of wakaf needs further regulation on the detail of the criteria and procedures for the validation so that the wakaf is still valid and provide legal certainty in the community.Key words: Stock Wakaf, Islamic Law, Legislation